The combination of psychosocial working conditions, occupational balance and sociodemographic characteristics and their associations with no or negligible stress symptoms among Swedish occupational therapists - a cross-sectional study - Carita Håkansson; Annika Lexén (BMC, 2021)
Abstract Background The numbers of people who are on sick leave due to mental health problems, such as exhaustion disorder, are increasing in Sweden. One of the most affected groups is healthcare professionals. In order to develop preventive strategies to promote a sustainable working life for occupational therapists, there is a need to understand the associations between psychosocial working conditions, occupational balance and no or negligible stress symptoms. To the best of our knowledge, neither the combination of these factors nor the salutogenic perspective, have been taken into consideration when exploring factors associated with stress symptoms among occupational therapists in previous research. Methods Purposeful sampling was used. All currently working members of the Swedish Association of Occupational Therapists were invited to take part in the present study in 2018. The final sample was 3658 (48% response rate). A web-survey with questions about signs of exhaustion, psychosocial working conditions, occupational balance and sociodemographic characteristics was used. Logistic regression analyses were used in order to calculate associations between psychosocial working conditions, occupational balance, sociodemographic characteristics and no or negligible signs of exhaustion. Results Experiencing high occupational balance, low workload, high control, high sense of community and high justice, were associated with no or negligible stress symptoms. Furthermore, a satisfying financial situation, having children living at home, being married and long professional experience were significant in this model. Conclusions It seems important to consider not only psychosocial working conditions, but also occupational balance to prevent exhaustion disorder among occupational therapists in Sweden. Organisational programmes, which reduce the workload, strengthen the control and sense of community and facilitate occupational balance, seem to be important areas for health promotion in this group.